Pengaruh Komposisi Bahan Organik terhadap Pertumbuhan Maggot Hermetia illucens (Black Soldier Fly): The Effect of Organic Matter Composition on the Growth of Maggot Hermetia illucens (Black Soldier Fly) - Liswara Neneng; Stevin Angga; Rio Eka D.P. Hartanti; Frenklin Yuda Laba; Gamaliel Gamaliel; Dicky Satriya Pratama (FKIP, Universitas Palangka Raya, 2023)
The Black Soldier Fly (BSF) larvae, commonly known as maggot, have gained attention as an alternative source of protein for animal feed. Nutrition is a crucial factor in the growth of BSF larvae, and different organic materials have varying nutritional contents. This study aims to investigate the effect of different types and combinations of organic materials on the growth of BSF maggot and to determine the optimal type and combination for their growth. The results of the study indicate that a combination of rice bran and fruit/vegetable waste (50:50) provides the best growth for BSF maggot with an average weight of 454 g. A combination of rice bran and tofu dregs (50:50) yields a growth rate of 447 g, and chicken manure (100%) yields a growth rate of 435 g. These findings can serve as a reference for the development of alternative maggot-based feed in the livestock industry.